#### My Profile

1. Inform you about time table of exam.

2. Inform you about new question papers.

3. New video tutorials information.

#### Question

Prove the following identities:

`(i) 2 (sin^6 θ + cos^6 θ) –3(sin^4 θ + cos^4 θ) + 1 = 0`

`(ii) (sin^8 θ – cos^8 θ) = (sin^2 θ – cos^2 θ) (1 – 2sin^2 θ cos^2 θ)`

#### Solution

#### Similar questions VIEW ALL

Prove the following identities, where the angles involved are acute angles for which the expressions are defined.

`(cos A-sinA+1)/(cosA+sinA-1)=cosecA+cotA`

Prove the following identities, where the angles involved are acute angles for which the expressions are defined

`(sin theta-2sin^3theta)/(2cos^3theta -costheta) = tan theta`

If sinθ + cosθ = p and secθ + cosecθ = q, show that q(p^{2} – 1) = 2p

Choose the correct option. Justify your choice.

(secA + tanA) (1 − sinA) =

A) secA

(B) sinA

(C) cosecA

(D) cosA

`"If "\frac{\cos \alpha }{\cos \beta }=m\text{ and }\frac{\cos \alpha }{\sin \beta }=n " show that " (m^2 + n^2 ) cos^2 β = n^2`